A Broadband View of the Sea Surface Height Wavenumber Spectrum. Issue 4 (16th February 2022) - Villas Bôas, Ana B.; Lenain, Luc; Cornuelle, Bruce D.; Gille, Sarah T.; Mazloff, Matthew R.
Abstract: Airborne lidar altimetry can measure the sea surface height (SSH) over scales ranging from hundreds of kilometers to a few meters. Here, we analyze the spectrum of SSH observations collected during an airborne lidar campaign conducted off the California coast. We show that the variance in the surface wave band can be over 20 times larger than the variance at submesoscales and that the observed SSH variability is sensitive to the directionality of surface waves. Our results support the hypothesis that there is a spectral gap between meso‐to‐submesoscale motions and small‐scale surface waves and also indicate that aliasing of surface waves into lower wavenumbers may complicate the interpretation of SSH spectra. These results highlight the importance of better understanding the contributions of different physics to the SSH variability and considering the SSH spectrum as a continuum in the context of future satellite altimetry missions. Plain Language Summary: Using unique measurements of the sea surface height (SSH) taken from an instrument onboard an airplane off the California coast, we examine how the variance of the SSH is distributed across different spatial scales, ranging from hundreds of kilometers to a few meters. We show that surface waves can be 20 times more energetic than motions with larger scales (known as submesocales) and that the direction of surface waves impacts the SSH variability depending on different sampling and averaging strategies. These results highlight the importance of better understanding the contributions of different types of motions and physics to the SSH variability. In particular, we advocate measuring scales from meters to hundreds of kilometers as a continuum to better inform future satellite altimetry missions. Key Points: We present unique broadband airborne lidar observations of sea surface height spanning scales from hundreds of kilometers to a few meters The sea surface height variance due to surface waves can be over an order of magnitude larger than the variance at submesoscales The observed sea surface height is sensitive to the direction of waves which may impact the interpretation of remote sensing measurements